2010
DOI: 10.1093/hmg/ddq056
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies polymorphisms in LEPR as determinants of plasma soluble leptin receptor levels

Abstract: Plasma soluble leptin receptor (sOB-R) levels were inversely associated with diabetes risk factors, including adiposity and insulin resistance, and highly correlated with the expression levels of leptin receptor, which is ubiquitously expressed in most tissues. We conducted a genome-wide association study of sOB-R in 1504 women of European ancestry from the Nurses' Health Study. The initial scan yielded 26 single nucleotide polymorphisms (SNPs) significantly associated with sOB-R levels (P < 5 x 10(-8)); all m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 42 publications
3
46
0
7
Order By: Relevance
“…17 In humans, circulating soluble OB-R is formed by ectodomain shedding of membrane-anchored OB-R. 18 , 19 There is strong association between sOB-R levels and 3 SNPs (including rs2767485, rs1751492, and rs4655555) in LEPR gene according to the fi nding of a recent genomewide association study, which indicated the role of LEPR as a candidate gene for regulating sOB-R levels. 13 In current study, we observed that AIS patients had significantly higher frequency of both TT genotype and T allele of rs2767485 polymorphism in LEPR gene than normal controls, which supported our prior fi nding that patients with AIS have signifi cantly higher sOB-R level than normal healthy girls. 7 As the main binding protein for leptin in the circulation, sOB-R might affect the leptin bioavailability to the cells by competing with membrane-anchored LEPR and inhibiting the transport of free leptin into cells and across the blood-brain barrier.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…17 In humans, circulating soluble OB-R is formed by ectodomain shedding of membrane-anchored OB-R. 18 , 19 There is strong association between sOB-R levels and 3 SNPs (including rs2767485, rs1751492, and rs4655555) in LEPR gene according to the fi nding of a recent genomewide association study, which indicated the role of LEPR as a candidate gene for regulating sOB-R levels. 13 In current study, we observed that AIS patients had significantly higher frequency of both TT genotype and T allele of rs2767485 polymorphism in LEPR gene than normal controls, which supported our prior fi nding that patients with AIS have signifi cantly higher sOB-R level than normal healthy girls. 7 As the main binding protein for leptin in the circulation, sOB-R might affect the leptin bioavailability to the cells by competing with membrane-anchored LEPR and inhibiting the transport of free leptin into cells and across the blood-brain barrier.…”
Section: Discussionsupporting
confidence: 89%
“…12 Previous studies had reported higher sOB-R level in patients with AIS, 7 and genome-wide association study had also identifi ed genetic determinants of plasma sOB-R levels in LEPR gene. 13 Hence, we conducted this casecontrol study to investigate whether the polymorphisms of LEPR gene were associated with inherent genetic susceptibility to AIS.…”
mentioning
confidence: 99%
“…A genome-wide association study has suggested a role for the LEPR Lys109Arg polymorphism as a regulator of LEPR plasma levels [26]. However, Oliveira et al [13] found that the LEPR Lys109Arg variant was associated with increased TC and TG, suggesting its contribution to the induction of an atherogenic lipid profile in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The A allele of the LEPR gene may contribute to changes in HDL-C levels by regulating hepatic lipase, phospholipid transfer protein, cholesteryl ester transfer protein, and/or lipoprotein lipase [29]. Sun et al [26], treated CAD patients with simvastatin (a HMG-CoA reductase inhibitor), and found that the increases in HDL-C in AA subjects were lower than in GG subjects. Treatment with statins and HC/LF diets may have a different mechanism in modulating the HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…Five SNPs associated with: serum amyloid A (rs1275319, (18)), soluble Ob-R (rs2767485, (19)), and CRP: (rs4420065 (20), rs6700896 (21) and rs1892534 (22) were forced in. From 412 cases (Supplementary Table 1), DNA was extracted from buffy coat using QIAGEN QIAmp and whole genome amplified using GE Healthcare GenomiPhi.…”
Section: Methodsmentioning
confidence: 99%